2014
DOI: 10.1371/journal.pone.0095968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amifostine in Head and Neck Cancer Patients Treated with Radiotherapy: A Systematic Review and Meta-Analysis Based on Randomized Controlled Trials

Abstract: BackgroundAmifostine is the most clinical used chemical radioprotector, but its effect in patients treated with radiation is not consistent.MethodsBy searching Medline, CENTRAL, EMBASE, ASCO, ESMO, and CNKI databases, the published randomized controlled trials (RCTs) about the efficacy of amifostine in HNSCC patients treated with radiotherapy were collected. The pooled efficacy and side effects of this drug were calculated by RevMan software.ResultsSeventeen trials including a total of 1167 patients (604 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 43 publications
1
64
0
4
Order By: Relevance
“…Amifostine is a sulfhydryl-containing compound. It is the only RA that has been approved by Food and Drug Administration of the USA [98] and the most commonly used RA in clinic, protecting the normal tissue via the scavenging of free radicals [99,100] . Having the characteristic of an ideal RA, it is of note that amifostine does not protect the tumor tissue [101] .…”
Section: Ra Its Categoris and Mechanisms Of Functionmentioning
confidence: 99%
“…Amifostine is a sulfhydryl-containing compound. It is the only RA that has been approved by Food and Drug Administration of the USA [98] and the most commonly used RA in clinic, protecting the normal tissue via the scavenging of free radicals [99,100] . Having the characteristic of an ideal RA, it is of note that amifostine does not protect the tumor tissue [101] .…”
Section: Ra Its Categoris and Mechanisms Of Functionmentioning
confidence: 99%
“…Cette molécule peut être administrée par voie veineuse ou souscutanée, mais seule l'administration intraveineuse a l'autorisation de mise sur le marché (AMM) en France [95]. Gu et al ont récem-ment publié une méta-analyse sur données publiées reprenant 17 essais sur 1167 patients étudiant les effets de l'amifostine dans l'irradiation dans cancers des voies aérodigestives supérieures [96]. En cas d'ajout de l'amifostine, ils ont montré une réduction du risque de mucite de grade 3-4 (risque relatif [RR] : 0,72 ; IC 95 % : 0,54-0,95, p < 0,00001), de xérostomie aiguë de grade 2-4 (RR : 0,70, IC 95 % : 0,52-0,96, p = 0,02), de xérostomie tardive de grade 2-4 (RR : 0,60, IC 95 % : 0,49-0,74, p < 0,00001) et de dysphagie de grade 3-4 (RR : 0,39, IC 95 % : 0,17-0,92, p = 0,03).…”
Section: Radioprotecteursunclassified
“…These authors stated that daily intravenous amifostine was associated with a high rate of serious adverse effects leading to discontinuation of the drug and sometimes delay in RT. Recent studies, however, have demonstrated that subcutaneous administration of amifostine was as effective as intravenous administration and safer considering toxicity [26,27]. Further research on the benefits of using subcutaneous amifostine is still required.…”
Section: Xerostomia Prevention Therapies Amifostinementioning
confidence: 99%